Writing Ability Improvement on EFL Students Using Think Pair Share Technique - Huwaida, Nisrina Balqis (ELLITE, 2017)
This research was to find out the effective way using think pair share techniqueto improve the students’ ability in writing analytical exposition text. The designof this research is Classroom Action Research. The research subject is XI Bclass consisting of 30 students. The data collected by using writing test, fieldnote and documment. In order to analyze the data students’ writing score,percentage formula is used. The researcher used only one cycle which consistof two meetings. Those the result of this cycle achieved the criteria of success.Think Pair Share technique improved the students’ writing ability in one cyclefrom the percentage of the students’ score ≥ 75 ( E= 83%). It is concluded thatThink Pair Share Technique can improve the Eleventh grade students’ writingability at Islamic Boarding School Baitul Arqom in the 2016/ 2017 academicyear by involving the students working in pair and sharing the ideas. So that they can discuss their writing draft and revise the writing product.